Practicing Critical Pedagogy The Influences of Joe L. Kincheloe - Agnello, Mary Frances; Reynolds, William Martin (Critical Studies of Education, 2016)
This edited text recaptures many of Joe L. Kincheloe's national and international influences. An advocate and a scholar in the social, historical, and philosophical foundations of education, he dedicated his professional life to his vision of critical pedagogy.  The authors in this volume found mentorship, as well as kinship, in Joe and express the many ways in which he and his work made profound differences in their work and lives. Joe's research always pushed the limits of what critically reflective and informed teaching entailed, never diluting the import of comprehending the complexity of sociopolitical, cultural, economic, and educational discourses and practices. Dedicated to a praxis of social and political activism rooted in students' development as citizens and workers, the labor of teachers as action researchers, cultural workers, and social mediators is always at the heart of all he achieved. We who were so influenced directly and indirectly by him knew his genius and relished the generosity with which he shared his ideas, advice, encouragement, and art. The world is better because of Joe L. Kincheloe scholarship-inextricably related to "critical" critical thinking and enactment of education that tenaciously interrupts complacency, mediocrity, always responding thoughtfully to particular educational contexts.